Analysis of leaflet flutter in biological prosthetic heart valves using PIV measurements - Avelar, Artur Henrique de Freitas; Stófel, Mairon Assis Guimaris Eller; Vieira, Glenda Dias; Canestri, Jean Andrade; Huebner, Rudolf (Acta Scientiarum. Technology, 2019)
The use of biological prosthetic valves has increased considerably in recent decades since they have several advantages over mechanical ones, but they still possess the great disadvantage of having a relatively short lifetime. An understudied phenomenon is the flutter effect that causes oscillations in the cusps, which is associated with regurgitation, calcification and fatigue, which can reduce even more the lifetime of bioproteses. In an experimental bench that simulates the cardiac flow, the behavior of a porcine and a bovine pericardium valves was recorded by a high-speed camera to quantify the oscillations of the cusps and an experiment using particle image velocimetry was conducted to study the velocity profiles and shear stresses and their relations with flutter. Results showed that the pericardial valve has lower values of frequencies and amplitudes compared to the porcine valve. Lower velocity values were found in the cusps that did not have flutter, but no relationship was observed between shear stress values and leaflet vibrations. These results may assist in future projects of biological prosthetic valves that have less flutter and longer lifespan.